2021
DOI: 10.1111/jgs.17022
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Long‐Term Care Staff to Receive a COVID‐19 Vaccine: A Single State Survey

Abstract: Objectives To plan for coronavirus infectious disease 2019 (COVID‐19) vaccine distribution, the Indiana Department of Health surveyed nursing home and assisted living facility staff. Design Cross‐sectional analysis of an anonymous survey sent via text message link to personal cell phones and emails. Setting and Participants Nursing home and assisted living facility staff in Indiana. Measures Staff characteristics including age, gender, race, ethnicity, role in the facility, experience in long‐term care, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
6
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(182 citation statements)
references
References 9 publications
6
157
6
9
Order By: Relevance
“…An American study of 11,460 care homes found only 37.5% of staff members had received a COVID-19 vaccine, compared to 77.8% of their residents [12]. Only one study has investigated COVID-19 hesitancy levels in care home staff (in Indiana, USA) [13]. In this study, 36% were reluctant, with the main barrier being concerns about side effects.…”
Section: Introductionmentioning
confidence: 91%
“…An American study of 11,460 care homes found only 37.5% of staff members had received a COVID-19 vaccine, compared to 77.8% of their residents [12]. Only one study has investigated COVID-19 hesitancy levels in care home staff (in Indiana, USA) [13]. In this study, 36% were reluctant, with the main barrier being concerns about side effects.…”
Section: Introductionmentioning
confidence: 91%
“…Using an online survey of American adults, Reiter et al found that participants were more likely to get vaccinated when they perceived a higher likelihood of getting a COVID-19 infection in the future, perceived a heightened severity of COVID-19 infection and perceived greater effectiveness in a COVID-19 vaccine; they were less likely to get vaccinated when they perceived higher potential vaccine harm [5]. Several studies have also been carried out on special populations, such as healthcare workers, long-term care staff and caregivers, which found that concerns about vaccine safety, side effects and effectiveness were the primary reasons for vaccine hesitancy [7,[10][11][12][13]. A Chinese national online survey found that participants that perceived the benefits and were unconcerned about the efficacy of COVID-19 vaccines had the highest intention to vaccinate [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, another study by Verger et al reported that 48.6% of the medical staff would de nitely be willing to undergo COVID-19 vaccination [20], while Unroe et al showed that 45% of the medical staff expressed willingness for COVID-19 vaccination [12]. Compared to the aforementioned studies focusing on foreign medical staff, the current found relatively higher willingness for vaccination among medical staff in China.…”
Section: Discussionmentioning
confidence: 70%
“…The COVID-19 pandemic has certainly placed a considerable burden on the global health care system [10]. Medical workers, especially nurses who most frequently come in contact with patients, are at high risk for COVID-19 infection [11,12]. Health personnel immunisation can be an approach to reduce the spread of pathogens and reduce personnel and labour costs during the pandemic [13].…”
Section: Introductionmentioning
confidence: 99%